ANALISIS MANAJEMEN LABA DALAM TINJAUAN ETIKA BISNIS ISLAM - Dilla Jannatul Khoiri; Della Prisca Devi Astriyasana; Mukhamad Rizal Fahmi; Fredi Pratama; Ardyan Firdausi Mustoffa (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
Financial reports have enormous benefits for their users, therefore they have become rules in the financial reporting process called GAAP (Generally Accepted Accounting Principles). The aim is to unify the process of financial reporting and reporting across all business units in the country, which will facilitate the process of checking the fairness of reporting. Despite these rule limitations, business leaders use performance management whether it is legal or not. To emphasize the importance of ethical Islamic income management, this article incorporates an Islamic perspective on income. The research in this study is based on and desk research which includes references to Islam, Islamic writings, and topics related to Islamic governance and ethics. The research design uses a descriptive reference/literature review method with reference to references on Islam, Islamic business, and matters relating to earnings management and Islamic business ethics.